Serum concentrations of indicator PCB congeners in the Czech adult population - Cerná, Milena; Malý, Marek; Grabic, Roman; Batáriová, Andrea; Smíd, Jirí; Benes, Bohuslav (Chemosphere, 2008)
In 2006, levels of seven indicator polychlorinated biphenyl congeners (PCB28, 52, 101, 118, 138, 153, and 180) in blood serum of 202 blood donors residing for more than 2 years in five urban areas included in the Czech Human Biomonitoring project were measured by GC/MS/MS method. PCB congeners 138, 153 and 180 accounted for about 97% of the sum of the indicator congeners analyzed. Overall, the median and 95th percentile of the most abundant congener PCB 153 were 438 ng/g lipid and 1079 ng/g lipid, respectively. The highest median levels were found in Uherské Hradiste (669 ng/g lipid) and Ostrava (672 ng/g lipid in males compared to 341 ng/g lipid in females). Serum PCB concentrations were significantly associated with age, gender, place of residence and smoking habit, but not with body mass index and education. The results suggest the importance of PCB body burden in the Czech general population and the existence of hot spots.
Keywords: dospělí; Female; Geography; Polychlorinated Biphenyls; Age Factors; Adult; ženské pohlaví; polychlorované bifenyly; Adolescent; věkové faktory; lidé; zeměpis; Sex Factors; Male; Aged; sexuální faktory; plynová chromatografie s hmotnostně spektrometrickou detekcí; Czech Republic; Environmental Pollutants; index tělesné hmotnosti; vystavení vlivu životního prostředí; Česká republika; Gas Chromatography-Mass Spectrometry; lidé středního věku; senioři; mužské pohlaví; látky znečišťující životní prostředí; Body Mass Index; Environmental Exposure; Middle Aged; mladiství; Humans